2005
DOI: 10.1074/jbc.m502144200
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Functionality of Common APOA5 Polymorphisms

Abstract: Common variants of APOA5 have consistently shown association with differences in plasma triglyceride (TG) levels. These single nucleotide polymorphisms (SNPs) fall into three common haplotypes: APOA5*1, with common alleles at all sites; APOA5*2, with rare alleles of ؊1131T3 C, ؊3A3 G, 751G3 T, and 1891T3 C; and APOA5*3, distinguished by the c56C3 G (S19W). Molecular modeling of the apoAV signal peptide (SP) showed an increased angle of insertion (65°) at the lipid/water interface of Trp-19 SP compared with Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 38 publications
7
92
0
5
Order By: Relevance
“…The present study was too small to perform meaningful haplotype analyses, but it has been suggested that the minor allele of the APOA1 promoter polymorphism is on the same haplotype as the minor allele of c56C→G, which could provide an explanation for the observed relationship [30]. The S19W (c56C→G) polymorphism located in the signal peptide is predicted to have an effect on APOA5 gene transcription [33], whereas results from in vitro expression studies suggested that the −1131T→C may not be a functional polymorphism [33]. However, we do find a significant association with plasma APOA5 levels, although in the opposite direction to the c56C→G polymorphism.…”
Section: Discussionmentioning
confidence: 72%
“…The present study was too small to perform meaningful haplotype analyses, but it has been suggested that the minor allele of the APOA1 promoter polymorphism is on the same haplotype as the minor allele of c56C→G, which could provide an explanation for the observed relationship [30]. The S19W (c56C→G) polymorphism located in the signal peptide is predicted to have an effect on APOA5 gene transcription [33], whereas results from in vitro expression studies suggested that the −1131T→C may not be a functional polymorphism [33]. However, we do find a significant association with plasma APOA5 levels, although in the opposite direction to the c56C→G polymorphism.…”
Section: Discussionmentioning
confidence: 72%
“…4 A peroxisome proliferator response element is present in the promoter region of APOA5, 42 but a functional effect of this SNP has not been demonstrated in studies in a luciferase reporter assay. 43 Instead, its effect could be due to strong linkage with functional variants in the nearby APOC3 gene. 43,44 In conclusion, our study shows convincingly in two large independent populations that one SNP only, namely rs662799, is a major determinant of plasma triglyceride levels in Chinese, independent of other known determinants of triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…43 Instead, its effect could be due to strong linkage with functional variants in the nearby APOC3 gene. 43,44 In conclusion, our study shows convincingly in two large independent populations that one SNP only, namely rs662799, is a major determinant of plasma triglyceride levels in Chinese, independent of other known determinants of triglyceride levels. As hypertriglyceridaemia is recognized as a risk factor for coronary heart disease and stroke, 45 this SNP may influence the susceptibility of the individual to cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Because APOA5 expression is downregulated by SREBP1c (20 ), we assume that apo A-V plays a determining role in PI-induced hyperlipidemia. Whether the -1131C allele is a functional variant or is acting as a marker of a functional variant elsewhere in the gene is not clear (21 ).…”
Section: Apoa5 Enhances Pi-associated Hyperlipidemiamentioning
confidence: 99%